Dignity at Work for Low Wage, Low Skill Service Workers - Berg, Peter; Frost, Ann (Relations industrielles / Industrial Relations, 2005)
Using responses from a telephone survey of 589 low wage, low skill workers in US hospitals, the authors investigate the workplace features that influence workers’ perceptions of dignity at work. Both work organization variables and union representation are investigated as potential factors affecting workers’ perceptions of fair treatment by their employer, intrinsically satisfying work, and economic security. Work organization and union representation have little effect on dignity at work with the exception of their association with higher wages and therefore a greater degree of economic security. Results indicate that higher pay, adequate levels of staffing and resources, and access to training are the variables that are most closely associated with dignity on the job.